First steps towards FAIRization of product-focused sensory data. (March 2023) - Visalli, Michel; Schlich, Pascal; Mahieu, Benjamin; Thomas, Arnaud; Weber, Magalie; Guichard, Elisabeth
Highlights: A data-centric typology of sensory evaluation measures was proposed. Sensory evaluation methods were classified using the typology. Minimum information standards were proposed for reporting sensory measures. Interests and limits of sensory data aggregation were discussed. Foundations for the FAIRization of product-focused sensory data were laid. Abstract: The emergence of open science makes it necessary to formalize data and knowledge in a way that adheres to the FAIR (Findable, Accessible, Interoperable, Reusable) principles. The objective of this work was to lay the foundations for such a FAIRization of sensory data. After an explanation of the rationale, the main characteristics of sensory evaluation methods were identified, and a data-centric typology of the different types of measures was proposed. This typology enabled us to classify the sensory evaluation methods regardless of whether they were used in "sensory only" or "consumer-centric product-focused" research. To complete this conceptual typology, minimal information standards have been defined to help in the reporting and interpreting of sensory evaluation data. These standards include a data format and metadata related to sensory evaluation measures. Based on the typology and metadata, several aspects related to sensory data aggregation were discussed, and examples were presented to demonstrate the interest of such a grouping of datasets. The outputs of this work were intended to be implemented in the "sensory evaluation measures" branch of TransformON, a food ontology. Thus, this work opens up new perspectives related to the use of ontologies for data-driven research related to food sustainability. Moreover, it invites the sensory science community to adopt a broader perspective regarding sensory measures.